2020
DOI: 10.3329/ralf.v6i3.44802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spacing on the performance of newly developed Aus rice Var. Binadhan-19

Abstract: Binadhan-19Row spacing Plant densityYield attributes Yield An experiment was conducted at the experimental farm of BINA Sub-station, Gopalganj to determine the effect of spacing on the yield and yield attributing parameters of rice. Four spacings viz. 15 cm × 15 cm, 20 cm × 15 cm, 20 cm × 20 cm and 25 cm × 20 cm were included in the study. The experimental design was a randomized completely block with three replications. Spacing's 15 cm × 15 cm, 20 cm × 15 cm, 20 cm × 20 cm and 25 cm × 20 cm were adopted 49, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…This might be due to the net effect of other attributes contributing to yield, like the number of plants per plot, as more spacing between the plants will automatically limit the total number of plants in a field or plot. Similar findings were reported by Rajesh and Thanunathan (2003) and Akondo and Hossain (2019) in their experimental studies. Dunn et al (2020) also found higher yields from lower plant density than greater plant density in their field experiment.…”
Section: Effect Of Spacing On Grain Yieldsupporting
confidence: 92%
See 4 more Smart Citations
“…This might be due to the net effect of other attributes contributing to yield, like the number of plants per plot, as more spacing between the plants will automatically limit the total number of plants in a field or plot. Similar findings were reported by Rajesh and Thanunathan (2003) and Akondo and Hossain (2019) in their experimental studies. Dunn et al (2020) also found higher yields from lower plant density than greater plant density in their field experiment.…”
Section: Effect Of Spacing On Grain Yieldsupporting
confidence: 92%
“…Greater spacing might have resulted in maximum utilization of nutrients, which led to more cell elongation and cell division in the meristematic tissue of plants, which play a key role in increasing plant height. These results are in accordance with the findings of Akondo and Hossain (2019). Further, Ogbodo et al (2010) also observed that plant height was significantly higher when crops were transplanted at a wider spacing (30 cm × 30 cm) than at a closer spacing (10 cm × 10 cm and 20 cm × 20 cm).…”
Section: Agronomic Characters 311 Plant Heightsupporting
confidence: 89%
See 3 more Smart Citations